COMPARISON OF SIMPLE ALGORITHM DATA (SORTING) CONTROL METHODS ON SELECTION AND BUBBLE SORT - Bustami Bustami; Fadlisyah Fadlisyah; Gusti Alfyansyah (Teknik Informatika Universitas Malikussaleh, 2019)
In the data there is a sorting process which is sorting data with certain rules, so that it will be arranged in the algorithm. Algorithms are steps that will solve a problem in the data, algorithms have a variety of settlement methods, one of which is the sorting method. Data sorting (Sorting) contains different types such as Bubble Sort, Insertion Sort, Merge Sort, Quick Sort, Selection Sort, and Shell Sort. The following will explain how to process the data sequencing of each method using a simple algorithm, especially in the Selection Sort method, and Bubble Sort. Keywords: Algorithm, Bubble Sort, Selection Sort